Immunotherapy for canine cancer – Is it time to go back to the future?. (23rd February 2015) - Killick, D. R.; Stell, A. J.; Catchpole, B.
Abstract : Over the last 50 years, the significance of the immune system in the development and control of cancer has been much debated. However, recent discoveries provide evidence for a role of immunological mechanisms in the detection and destruction of cancer cells. Forty years ago veterinary oncologists were already investigating the feasibility of treating neoplasia by enhancing anticancer immunity. Unfortunately, this research was hindered by lack of a detailed understanding of cancer immunology, this limited the specificity and success of these early approaches. The great forward strides made in our understanding of onco‐immunology in recent years have provided the impetus for a resurgence of interest in anticancer immunotherapy for canine patients. In this article both these initial trials and the exciting novel immunotherapeutics currently in development are reviewed.